ثلاثیات الأمام الدارمي دراسة وتخریج (Journal of the College of Education for Women, 2019)
After this trip start to get interesting conclusion, conclusion and maintenance station,the conclusion, where we summarize the most important findings:1. We found that the triads are the conversations that will be assigned in three narratorsbetween the workbook and the Prophet.2. The number of triangles is the Imam recaps (15) recently, and all true only recently onewell in the Book of Rites and the modern were weak in the book authorization and the Book ofVirtues of the Quran.3. Triads varied in the ways of drama at the gates of Islamic jurisprudence, he may talk andone each from the Book of purity and prayer, fasting, marriage and the tortillas and the virtuesof the Quran, and has had three conversations in each of the Book of Rites and polite andsales.4. And diversity as well as the lesson of this hadith, hadeeth is da'eef purity and stood it onthe kindness of the Prophet in his dealings with his companions, and kindness to them, aswell as the capacity of the chest-Sharif and his humility as began clearing the mosque honestin his hand; It transpires that a great reward for clearing the mosque and clean it.5. And modern hate slugs him in the mosque Vostvid literature with Allah (U), and as long asthe person in prayer, he is in monologue with God, and that the Prophet minutes things welearned our religion did not leave us something even etiquette slugs.6. In an interview guide on the status of Ashura Day of Ashura, and the significance of thatintent is not required Etbitha.7. In conversations stoning ritual that is valid in any case, walking or riding, and is required forUmrah Tawaf and seek between Safa and Marwah. And a keen love for the prophet and theprophet .8. In an interview with the wedding feast, the feast that is subject to mustahabb least a solventand a sheep on the other to the extent of it and after entry.9. In an interview with taxi cupper benefit from it is permissible to take the doctor for the taxi,and emphasize the importance of cupping and that the Prophet is often treated with cupping.10. In an interview with the boy who brings behind wives of the Prophet and stood too muchon command of the Prophet Baltervq women and Usith them good, and the use of theProphet the word bottles rather than women because of its impact on the listener, and it ispermissible to Alhaddae if safe from obscenity.11. In an interview with the virtues of the Quran is subject to Fadel Al-fidelity, as well as anychair, as well as the other two preferred the two verses of Sura, and it is permissible to preferone on another.and singing.